Effectiveness of Antiemetic Treatment Among Breast Cancer Patients in Inpatient Unit Sardjito General Hospital - Putri Ekasari, M; Munif Yasin, N; Ari Kristina, S; Ikawati, Z (KnE Life Sciences, 2019)
Nausea and vomiting are chemotherapy adverse events that influence breast cancer patient’s quality of life. Antiemetic regimen as premedication was given to prevent those adverse events and need to be evaluated. This study aimed to present the effectiveness of antiemetic treatment among breast cancer patients in the inpatient unit, Rumah Sakit Umum Pusat Dr. Sardjito [Central Public Hospital Dr. Sardjito] Yogyakarta, Indonesia. A cohort study was used in this study during July 2008 to January 2009. Thirty-one breast cancer patients, who are receiving antiemetic therapy and having no disease that induced nausea and vomiting were involved, signed informed consent and had been followed by before-post chemotherapy. The data was gained from chemotherapy and antiemetic regimens, medical records, patient’s interviews, and finally analyzed using descriptive, evaluative approach. This study presented that antiemetic treatment among breast cancer patient in the inpatient unit was 61.40 % ineffective reducing incidence of nausea vomiting events. The majority of cases of nausea and vomiting onset among patients were acute-delayed (56.2 %; 52.0 %), severity of nausea and vomiting laid mostly in the second level (54.54 %; 52.00 %), and appropriateness antiemetic treatment complied to NCCN guideline 2007 and ASCO guideline 2006 was only applied in low emetic risk of chemotherapy-induced nausea and vomiting. Antiemetic regimens that had been implemented need to be evaluated because of majority cases of nausea and vomiting were the acute-delayed type, level two of severity and inappropriateness of international guideline. This study should be followed with the future study of the evaluation of the effectiveness of another medication supported the patient in receiving chemotherapy. Keywords: Antiemetic, Breast cancer, Effectiveness, Nausea, Vomiting.